Effect of Feeding Time of BSF (Hermatia illucens) Larvae as Supplementary Feed on Growth and Survival Catfish Fry (Clarias sp): PENGARUH WAKTU PEMBERIAN LARVA BSF (Hermatia illucens) SEBAGAI PAKAN TAMBAHAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN LELE (Clarias sp) - Humeira; Nurul Najmi; Rahmaton Hayati; Kurnia; Ika Rezvani Aprita (ROCE : Jurnal Pertanian Terapan, 2024)
This research aims to determine the effect of the timing of feeding BSF larvae (Hermatia illucens) as additional feed on the survival and growth of catfish fry (Clarias sp). This research was conducted for 30 days in May - June 2019 at the Laboratory of the Fish Seed and Feed Production Technology Department, Politeknik Indonesia. The research method used in this study is an experimental method using a completely randomized design (CRD) consisting of four treatments and four replicates resulting in 16 experimental units with treatment A (Control) Adlibitum, B (BSF larvae in the morning) Adlibitum, C (BSF larvae in the afternoon) Adlibitum, and D (BSF larvae in the afternoon) Adlibitum. The provision of BSF larvae (Hermatia illucens) as additional food has a significant effect on survival, specific growth, relative growth, absolute length growth of catfish seeds (Clarias sp). The best treatment is found in treatment B, namely the provision of BSF larvae in the morning as additional feed with a specific growth rate of 0.05 grams/day, absolute length growth of 6.29 cm, relative growth value of 9.64%/day and feed conversion ratio of 0.63.